2010
DOI: 10.1007/s11095-009-0041-x
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Nanocarriers: Potential Nose-to-Brain Delivery of Zolmitriptan as Novel Migraine Therapy

Abstract: The investigation indicated the potential of the developed nanocarrier as an effective new-generation vehicle for brain targeting of zolmitriptan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…39%, 5.78%, 144.25, 3.46, and 99.3, 70.07 for intranasal 99m Tc-PM7 and intranasal 99m Tc-CZ solution, respectively. These results are in accordance with Jain et al (2010) and Kanazawa et al (2011) who found that intranasal PM have a very high potential for brain targeting of zolmitriptan and coumarin, respectively.…”
Section: Biodistribution Studysupporting
confidence: 92%
“…39%, 5.78%, 144.25, 3.46, and 99.3, 70.07 for intranasal 99m Tc-PM7 and intranasal 99m Tc-CZ solution, respectively. These results are in accordance with Jain et al (2010) and Kanazawa et al (2011) who found that intranasal PM have a very high potential for brain targeting of zolmitriptan and coumarin, respectively.…”
Section: Biodistribution Studysupporting
confidence: 92%
“…The DTI values >1 could confirm the direct pathway from nose to brain (Wang, Jiang, Lu, 2003). These findings are in line with Jain et al (2010), Kanazawa et al (2011) who found that micellar nanocarriers of zolmitriptan and coumarin increase the nose-to-brain uptake, via the olfactory region of the nasal cavity. Finally, the higher value of DTI, DTE (%) and DTP (%) suggested that HP-SLNs have better brain targeting potential as compared to HP-Sol administered intranasally.…”
Section: In Vivo Studies For the Determination Of Pharmacokinetic And Bsupporting
confidence: 85%
“…Direct transport of drugs to the brain circumventing the brain-barriers following intranasal administration provides a unique feature and better option to target drugs to the brain. Intranasal administration of ZT for direct transport to the brain via microemulsion (Vyas et al, 2005), polymeric microparticles (Gavini et al, 2013), nanoparticles (Girotra et al, 2016), and micellar nanocarriers (Jain et al, 2010) have been developed. ZT nasal spray was approved by the FDA in 2003.…”
Section: Introductionmentioning
confidence: 99%